Resolving the Complexity of Spatial Lipidomics Using MALDI TIMS Imaging Mass Spectrometry - Djambazova, Katerina V; Klein, Dustin R; Migas, Lukasz G; Neumann, Elizabeth K; Rivera, Emilio S; Van de Plas, Raf; Caprioli, Richard M; Spraggins, Jeffrey M (Analytical chemistry (Washington), 2020)
Lipids are a structurally diverse class of molecules with important biological functions including cellular signaling and energy storage. Matrix-assisted laser desorption/ionization (MALDI) imaging mass spectrometry (IMS) allows for direct mapping of biomolecules in tissues. Fully characterizing the structural diversity of lipids remains a challenge due to the presence of isobaric and isomeric species, which greatly complicates data interpretation when only / information is available. Integrating ion mobility separations aids in deconvoluting these complex mixtures and addressing the challenges of lipid IMS. Here, we demonstrate that a MALDI quadrupole time-of-flight (Q-TOF) mass spectrometer with trapped ion mobility spectrometry (TIMS) enables a >250% increase in the peak capacity during IMS experiments. MALDI TIMS-MS separation of lipid isomer standards, including backbone isomers, acyl chain isomers, and double-bond position and stereoisomers, is demonstrated. As a proof of concept, separation and imaging of lipid isomers with distinct spatial distributions were performed using tissue sections from a whole-body mouse pup.